F6H8 as an Intraoperative Tool and F6H8/Silicone Oil as a Postoperative Tamponade in Inferior Retinal Detachment with Inferior PVR - Gian Marco Tosi; Davide Marigliani; Tommaso Bacci; Napoleone Romeo; Angelo Balestrazzi; Gianluca Martone; Tomaso Caporossi (Journal of Ophthalmology)
Purpose. To evaluate the effectiveness and safety of perfluorohexyloctane (F6H8) for intraoperative flattening of the retina and of F6H8/silicone oil (SO) 1000 cSt as a postoperative tamponade for inferior retinal detachment with inferior proliferative vitreoretinopathy. Methods. This is a retrospective review of 22 patients who underwent pars plana vitrectomy using F6H8 as an intraoperative tool to flatten the retina. At the end of the surgery a direct partial exchange between F6H8 and SO 1000 cSt was performed, tamponing the eye with different ratios of F6H8/SO (70/30, 60/40, 50/50, 40/30, and 30/70). Anatomical and functional results and complications were evaluated over the follow-up period (mean 22.63 months). Results. F6H8 was efficacious for intraoperative flattening of the retina. Twenty-one of the 22 patients achieved a complete retinal reattachment. Postoperative visual acuity (VA) ranged from light perception to 20/70, with 72% of patients obtaining VA better than 20/400. No emulsification/inflammation was observed whatever the ratio of F6H8/SO used. With higher ratios of F6H8/SO (70/30 and 60/40) cloudiness of the tamponade was observed. A transparent mixture was present with all the other ratios. Conclusions. The surgical technique adopted is very simple and safe. The optimal F6H8/SO ratio seems to be between 50/50 and 30/70.